2013
DOI: 10.1177/1457496913490464
|View full text |Cite
|
Sign up to set email alerts
|

Fenestrated and Chimney Endografts for Juxtarenal Aneurysms: Early and Midterm Results

Abstract: The treatment of juxtarenal aortic aneurysms seems to be feasible by exploiting various endovascular techniques. Even with a low volume of cases, good immediate and short-term results can be achieved, especially with fenestrated endografts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The results in the existing literature include a report from our own group, with similar findings in early follow-up 7 . Despite the generally positive tone of most publications, several series have reported postoperative complication rates ranging from 0–35% 8, 2022 . Eight(20%) patients in this study experienced postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…The results in the existing literature include a report from our own group, with similar findings in early follow-up 7 . Despite the generally positive tone of most publications, several series have reported postoperative complication rates ranging from 0–35% 8, 2022 . Eight(20%) patients in this study experienced postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published series have shown 30-day mortality rates for fEVAR ranging from 1.4% to 4.1%. 7,20 Banno et al 5 reported similar 30-day mortality for fEVAR and chEVAR at 6.3% and 7.9%, respectively. ESAR offers patients who might otherwise only be considered for complex endovascular repair a less technically demanding endovascular alternative for shortneck AAA.…”
Section: Discussionmentioning
confidence: 90%
“…Based on core laboratory assessment, the type IA endoleak rate of 6.8% at 1 month after ESAR is on par with alternative endovascular repair options in this complex anatomy. 20 Contemporary studies of fEVAR have reported type IA endoleak rates between 0% and 3.6%, but they have been as high as 7.1% in early reports. 5,21 Similarly, type IA endoleak after chEVAR ranges from 0% to 7.7% in several studies.…”
Section: Discussionmentioning
confidence: 98%
“…Four trials 18,27,33,38 were included in the meta-analysis. The outcomes of technical success, 30-day mortality, types I and II endoleaks, target organ dysfunction, vascular restenosis/occlusion and re-intervention were analyzed (Figure 3).…”
Section: Resultsmentioning
confidence: 99%